1987
DOI: 10.1203/00006450-198702000-00007
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Receptors and Cyclic Adenosine Monophosphate Generation in Human Fetal Lung

Abstract: ABSTRACT. We designed experiments to determine whether P-adrenergic receptors are present and functional in human fetal lung during the 2nd trimester of gestation. To determine the presence of p receptors, characterize their binding sites, and assess changes in receptor with gestational age, we performed radioligand binding assays with the specific, high-affinity P antagonist, '251-iodocyanopindolol, in membrane particulates from the lungs of 2nd trimester abortuses (15-23 wk). Binding of '251-iodocyanopindolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…The difference between our studies and those in animals may simply reflect a difference between species in the effect of glucocorticoids on the P-adrenergic response cascade. The @,-receptor subtype, which predominates in rabbit fetal lung (I), may respond differently to dexamethasone treatment than the &receptor subtype, which predominates in human fetal lung (2,3). This could not explain the difference between rat and human fetal lung, both of which contain P2-receptors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The difference between our studies and those in animals may simply reflect a difference between species in the effect of glucocorticoids on the P-adrenergic response cascade. The @,-receptor subtype, which predominates in rabbit fetal lung (I), may respond differently to dexamethasone treatment than the &receptor subtype, which predominates in human fetal lung (2,3). This could not explain the difference between rat and human fetal lung, both of which contain P2-receptors.…”
Section: Resultsmentioning
confidence: 99%
“…Samples for determination of receptor concentration were frozen and stored at -70°C until membrane preparation. We have previously shown that under these conditions P-adrenergic receptor concentration was not different from that in fresh specimens (3). Samples for determination of cAMP generation were processed immediately after harvesting.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…epinephrine and dibutyryl-CAMP have a greater effect in causing lung liquid absorption toward term than they do earlier in gestation (1,4,5,14). Previous studies of the ontogeny of 0-adrenergic receptors in the lungs of several species, including sheep, indicate that the concentration of P-adrenergic receptors in the lung increases with advancing gestation (7,9,(16)(17)(18). In fetal sheep, the concentration of pulmonary P-adrenergic receptors doubles between 125 and 135 d gestation (7), which might account for the increased effect of terbutaline that we observed over this range of gestation.…”
Section: Mmol/l) Inmentioning
confidence: 99%